Executive decree to grant amnesty to officials and soldiers José Manuel Moreno, José María Alpuche é Infante, José Barrera, and Manuel Carbajal, Mexico City - Alamán, Lucas, 1792-1853 (Primera Secretaria de Estado. Departmento del Interior, 1830)
This s a decree issued by Lucas Alaman on behalf of Anastasio Bustamante, President of Mexico declaring amnesty for officials and soldiers: Jose Manuel Moreno, Jose Maria Alpuche, Jose Barrera and Manuel Carbajal for having supported the proclamation of Campeche as a central republic.